[Generics ; Biglang liko ; Film making [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Discusses the issues and implementation of Generic Act; the motels as pleasure point for lovers and film making as an art. Also includes interviews with Peque Gallaga on his film directing.